Environmental policy of Uzbekistan and measures to reduce CO₂ emissions - Нилуфар Р. Авезова; Ilimdor J. Jahongirov; Elvira A. Oshepkova (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: The Republic of Uzbekistan, as a party to the Paris Agreement, aims to reduce its CO₂ emissions intensity (per GDP unit) by 35% by 2030 compared to 2010 levels. To achieve this target, a comprehensive set of measures has been adopted: increasing the share of renewable energy sources in electricity generation to 54% by 2030, doubling economic energy efficiency, and conducting an extensive afforestation campaign (planting 1 billion trees within 5 years). Aim: analysis of methods for reducing the carbon intensity of the economy to the level of developed countries, development of recommendations for improving the effectiveness of environmental policy. Methods: the methodological basis of the country's climate policy is a combination of strategic planning, regulatory legal acts and institutions that ensure the implementation and control of emission reduction measures. Results: authors analyzed the effectiveness of these initiatives, provided quantitative assessments of emissions reductions, and developed recommendations to enhance the efficiency of environmental policies.